A realidade que se vê e a realidade que se vive : uma pesquisa de recepção sobre as representações sociais da favela e suas práticas de consumo na ficção televisiva brasileira - Alves, Virgínia Albuquerque Patrocínio (2017)
The present research has as its theme the social representation of favelas in Brazilian telenovelas from the point of view of the perception of the reality-fiction articulation by residents of favelas of São Paulo, focusing both on their daily experiences, intensely tied to the practices of material consumption, and reception of fictional media content. The theoretical-conceptual framework that gives base to the study develops in the interface between communication, identity and consumption. In order to deal with the social representation of the favela and the social construction of reality, we rely on the concepts founded by Moscovici and Berger and Luckmann, as well as Jaguaribe and Valladares, who helped us to understand the imaginary construction around the idea of ​​a favela along of the historical process in which it was established in the Brazilian urban scenario. When it comes to the development of television as an important cultural media product of the country, we work essentially with Tondato, Baccega, Lopes, Hamburger. The consumption perspective was based on the ideas of Garcia Canclini, Slater, Douglas and Isherwood, Alonso and Baccega. With a view to understanding how the formation and reiteration of social representations that give meaning to the daily life of slum dwellers and that structure their own notion of reality, as well as identifying how the media content acts in the mediation of the reality around them, we had as an empirical reference, the discourses given by the residents themselves in a reception research, carried out through focus groups with residents of favelas distinct from São Paulo. In summary, we have that the social representations function as formators of the perception of the reality in which they live and of the identities of local belonging. The results confirm that social representations significantly mark the reception of telenovelas and that systems of conventions previously established and socially accepted are expected in fiction as a way to reiterate them continuously.